Hyperfluorescence Imaging of Kidney Cancer Enabled by Renal Secretion Pathway Dependent Efflux Transport. Issue 1 (26th October 2020) - Du, Bujie; Chong, Yue; Jiang, Xingya; Yu, Mengxiao; Lo, U‐Gling; Dang, Andrew; Chen, Yu‐An; Li, Siqing; Hernandez, Elizabeth; Lin, Jason C.; Hsieh, Jer‐Tsong; Zheng, Jie
Abstract: Renal tubular secretion is an active efflux pathway for the kidneys to remove molecules but has yet to be used to enhance kidney cancer targeting. We report indocyanine green (ICG) conjugated with a 2100 Da PEG molecule (ICG‐PEG45) as a renal‐tubule‐secreted near‐infrared‐emitting fluorophore for hyperfluorescence imaging of kidney cancers, which cannot be achieved with hepatobiliary‐ and glomerular‐clearable ICG. This pathway‐dependent targeting of kidney cancer arises from the fact that the secretion pathway enables ICG‐PEG45 to be effectively effluxed out of normal proximal tubules through P‐glycoprotein transporter while being retained in cancerous kidney tissues with low P‐glycoprotein expression. Tuning elimination pathways and utilizing different efflux kinetics of medical agents in normal and diseased tissues could be a new strategy for tackling challenges in disease diagnosis and treatments that cannot be addressed with passive and ligand‐receptor‐mediated active targeting. Abstract : By switching the clearance route of indocyanine green (ICG) from liver uptake to renal tubular secretion with low molecular weight PEGylation, we were able to hyperfluorescently image kidney cancers and their metastases with no need for ligand‐receptor‐mediated active targeting.